Tuberculin reactivity in bacille calmette-guerin vaccinated individuals with sputum positive pulmonary tuberculosis - Jha, PK; Gurung, R; Gyawali, N; Nepal, HP; Baral, DD; Bhattacharya, SK (Journal of College of Medical Sciences-Nepal, 2012)
The study was carried out to assess the value of tuberculin skin test for the diagnosis of Tuberculosis (TB) in BCG vaccinated individuals and to find out the sensitivity rate of tuberculin skin test (TST) in comparison to acid fast bacilli positive pulmonary TB. Similar population with high BCG vaccination coverage having both pulmonary TB patients (n=150) and apparently healthy individuals (n=150) in eastern Nepal were enrolled in this comparative study. Sputum from all the subjects was subjected to Z-N microscopy. TST was performed on these subjects by standard Mantoux method. Among the patients (mean age 36.18±14.15 yrs) and controls (mean age 35.61±13.44 yrs), 55.33 % and 47.33 % respectively have been found to be positive PPD reactors (>10mm) which is statistically not significant (P>0.05). About 23% of the patients & 27% of controls failed to react (anergic) to 5 TU PPD. PPD reactivity rate was high in the patients whose sputum smears were graded as 1+ in Z-N microscopy. The sensitivity of TST was highest for the induration of >5mm (77.3%). Specificity increased with increasing size of induration and was highest (73.3%) with induration of >15 mm. Tuberculin skin test is an all or none phenomenon. In Nepal, tuberculin test has a limited value in the diagnosis of pulmonary TB as both the apparently healthy individuals and patients with sputum smear positive pulmonary TB who had been immunized with BCG, showed almost similar rate of tuberculin reactivity. DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5970 JCMSN 2011; 7(1): 28-35